Tokenised discretisation in iris verification - Chin, Chong Siew; J., Andrew Teoh B.; L., David Ngo C. (2005)
A novel authentication approach which based on the integration of tokenised pseudo-random numbers and the user's iris biometrics, to generate a user-specific binary bitstring via an iterated inner-product mechanism is proposed. The proposed method, S-Iris encoding, protects against iris fabrication as it can only contribute to the authentication process when both the genuine biometrics template and pseudo-random number are presented. It also enables straightforward revocation via token replacement. Furthermore, S-Iris Encoding reduces length of iris feature to around 5% of its original size yet able to attain an approximately 0% of Equal Error Rate (EER). This approach also shows the effectiveness and accuracy in term of verification rate if compared to the traditional biometrics system or the straightforward use of two authentication schemes in parallel.